THE EFFECT OF GREEN BRAND IMAGE, GREEN BRAND ATTITUDE, AND GREEN BRAND TRUST ON GREEN REPURCHASE INTENTION (CASE STUDY: THE BODY SHOP, INDONESIA) - Adventa Intan Pramesthi; Innocentius Bernarto (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to analyse the positive influence of green brand image, green brand attitude, and green brand trust on green repurchase intention. The survey method was implemented in this study. Questionnaires were used to collect data. The sampling technique in this study was purposive sampling. The sample size was 214 samples. Partial Least Square-Structural Equation Modeling (PLS-SEM) statistical tool was applied for data analysis. The results showed that green brand image has a positive effect on green repurchase intention. Then, green brand attitude has a positive effect on green repurchase intention. Finally green brand trust has a positive effect on green repurchase intention.